Studi Disolusi Terbanding Tablet Komparator dan Generik Glibenklamida 5 MG Menggunakan Parameter Difference Factor (f2) dan Similarity Factor (f1) - Sutriyo, Sutriyo; Aeni, Siti Nur; Sundarsih, Sundarsih (Majalah Ilmu Kefarmasian, 2012)
Dissolution testing is an essential requirement for the development, establishment of in Vitro dissolution and in Vivo performance (I VIV R), registration and quality control Of solid oral dosage forms. The objective of the present study was to compare dissolution profile of glibenclamide 5 mg tablet between generic and inovator product from commercial market, using independent model. Samples of glibenclamide 5 mg tablets was used on the batch number are the Same design for each other product. The dissolution test were perfoming using USP 23 apparatus 2, in pH 7,40 buffer phosphate, employing 900 ml of dissolution medium at a temperature of 37 ±0,5 ˚C and an agitation rate of 75 rpm with spesification performed at 15, 30, 45, 60 and 120 minutes. Comparison between dissolution profiles was achieved using a difference factor (f1) and simmilarity factor (f2) methods in inovator product and generic \ product. The results showed that dissolution profiles of product B (generic) has similar with product A (inovator) where difference factor (f1) value is 5,53% and simmilarity factor (f2) is 99,29 %